Efficacy of Alpha Keto-Analogues in The Management of Chronic Kidney Disease - Umar, Saba; Sabir, Sohail; Altaf, Ashfaq; Raja, Khalid Mahmood; Siddiqi, Fuad Ahmed; Saleem, Salman; Azam, Malik Nadeem; Sabir, Haroon (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the efficacy of alpha keto-analogues in the management of chronic kidney disease at a tertiary care hospital.Study Design: Quasi-experimental study.Place and Duration of Study: Nephrology Department, Armed Forces Institute of Urology, Rawalpindi from Jul to Dec 2020.Methodology: A total of 300 patients of chronic kidney disease stage 3 and 4, not dependent on hemodialysis were included in the study. They were divided into two groups with matched age, gender and duration of chronic kidney disease. Group-I received the routine treatment of chronic kidney disease with low protein diet while group-II received alpha keto-analogue in standard dose in addition to routine treatment of chronic kidney disease with low protein diet. Estimated glomerular filtration rate was assessed at the baseline and after six months.Results: Out of 300 patients 151 (50.3%) were males while 149 (49.7%) were female patients. 110 (36.7%) patients had stage-3 disease while 190 (63.3%) had stage-4 chronic kidney disease. Mean difference of eGFR in group-I was 3.17 ± 3.19 mL/min/ 1.73m2 while mean difference of eGFR in group-II was 1.16 ± 1.52 mL/min/1.73m2 (p-value